2020
DOI: 10.1002/smll.202002194
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Effects of Graphene and Molybdenum Disulfide on Human Macrophage Toxicity

Abstract: Graphene and other 2D materials, such as molybdenum disulfide, have been increasingly used in electronics, composites, and biomedicine. In particular, MoS2 and graphene hybrids have attracted a great interest for applications in the biomedical research, therefore stimulating a pertinent investigation on their safety in immune cells like macrophages, which commonly engulf these materials. In this study, M1 and M2 macrophage viability and activation are mainly found to be unaffected by few‐layer graphene (FLG) a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
31
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 36 publications
(35 citation statements)
references
References 54 publications
1
31
0
Order By: Relevance
“…Like what other researchers have reported with FLG in cellular TEM [33], there is a tendency for the presence of FLG to cause tearing of cell slices, inadvertently causing white space in the captured image and a decrease in image contrast, thereby losing visibility of many less prominent cell features such as keratin fibers. This has hindered more in-depth observations, like in other HaCaT studies showing autophagy induction, but which have featured non-graphene materials [34,35].…”
Section: Discussionsupporting
confidence: 55%
“…Like what other researchers have reported with FLG in cellular TEM [33], there is a tendency for the presence of FLG to cause tearing of cell slices, inadvertently causing white space in the captured image and a decrease in image contrast, thereby losing visibility of many less prominent cell features such as keratin fibers. This has hindered more in-depth observations, like in other HaCaT studies showing autophagy induction, but which have featured non-graphene materials [34,35].…”
Section: Discussionsupporting
confidence: 55%
“…For example, Zhang et al [ 15 ] observed the cytotoxic effect of a graphene nanosheet on neuronal PC12 cell lines, and Burgum et al [ 27 ] found the cytotoxic effect of few-layer pristine graphene on activated THP-1 cells. Lin et al [ 28 ] reported cytotoxic effects of few-layer graphene on primary macrophages, Lasocka et al [ 29 ] reported the cytotoxicity of pristine graphene monolayer without sharp edges on the murine fibroblast L929 cell line, Demir and Marcos [ 30 ] reported the cytotoxicity of graphene nanoplatelets on the mouse lymphoma cell line and Malanagahalli et al [ 31 ] reported the cytotoxicity of few-layer graphene on mouse macrophages. On the other hand, Zhang et al [ 15 ] did not find any significant damage to the cell membrane, and Luo et al [ 9 ] reported the absence of cytotoxicity of GO (smaller than 500 nm) regarding activated THP-1 cells.…”
Section: Discussionmentioning
confidence: 99%
“…[24,[28][29][30] KCs also provide the first line of defense against nanoparticles entering the systemic circulation. [24,31,32] Although it has been shown that MoS 2 and BN nanotubes induce cell stress or pro-inflammatory effects in human macrophages, [33][34][35] no systematic studies have been performed to address the effects of BN or MoS 2 nanosheets on KCs. In our previous studies looking at the impact of a variety of metal oxide (MOx) and rare earth oxide nanoparticles on KCs, we have demonstrated the utility of the immortalized KC line, KUP5, in providing a good readout of the toxic potential of nanomaterials on primary KC responses.…”
Section: Introductionmentioning
confidence: 99%